Investigation of Optical Properties and Electronic Transfer of Temperature-Dependent ZnO Nanocolumnars Grown by DC Sputtering - Robi Kurniawan; Intan Salsabila Mauludina Sari; Isnaini Yulianingtyas; Joyuhan Putra Setyawan; Ibrahim Nur Afrizal Dahlan M.; Resti Marlina; Joko Suwardy (JPSE (Journal of Physical Science and Engineering), 2022)
The morphology of zinc oxide (ZnO) can determine the distribution of defects in the system, which plays an important role in determining its optical and electronic properties. Here, we investigate the optical and electronic transfer properties of different ZnO surface morphologies. ZnO nanocolumnar was synthesized by direct-current (DC) sputtering followed by annealing using a ratio of T/Tm are 0.15, 0.20, and 0.25. The x-ray diffraction (XRD) results show that an increase in annealing temperature causes an increase in crystal size accompanied by a decrease in lattice strain. Furthermore, the surface morphology of the sample changed with increasing annealing temperature treatment, following the structural zone model. The optical and electronic transfer properties of the samples were investigated in three regions; region 1 (T/Tm is 0.15), region 2 (T/Tm is 0.20), and region 3 (T/Tm is 0.25) using optical modeling. The highest surface electronic transfer was noted in region 2, which is indicated by the highest surface energy loss function (SELF). This research can provide a good understanding in designing optoelectronic systems based on their morphological features.DOI: 10.17977/um024v7i22022p086